Aesthetics, affect, and making meaning in science education: an introduction. Issue 5 (24th March 2022) - Wickman, Per-Olof; Prain, Vaughan; Tytler, Russell
ABSTRACT: This overview gives a background for this special issue of the International Journal of Science Education on Aesthetics, affect, and making meaning in science education . Contributions to this special issue examine how and what kind of aesthetics of science is constituted when it meets the aesthetics of other practices (e.g. arts, mathematics, student lives), in and outside classrooms, and the consequences these encounters have for meaning-making and in learning science. It reviews various traditions and concepts used in studying aesthetics and affect in science education, their theoretical foundations and the different meanings these traditions assign to the concepts. The review spans from cognitivist, causal approaches to socio-culturally and pragmatically-oriented stances and examines the educational questions that these frameworks pose and resolve. The review makes a case that the socio-cultural and pragmatic frameworks adopted in the set of papers, focused on the continuity of aesthetic experience with meaning-making opens up fresh and powerful ways to support science teaching and learning. This review offers a backdrop against which the novelty of the individual contributions can be understood.